Investigation into the spatial distribution of salt loads into the Upper Thurne SAC and likely timescales for response to management controls - Heward-Mills, Christine (Cranfield University, 2013)
The Upper Thurne Broads (shallow lakes) in the Norfolk Broads are sites of international conservation importance. The protected aquatic species of these lakes are currently threatened by poor water quality, largely due to discharges of saline water from the Brograve land drainage pump, which maintains groundwater levels on adjacent marshlands below sea level. The lowering of water table levels by drainage has caused seawater to intrude into the coastal aquifer and salinise the groundwater and drain network. Through surveying salt concentrations and flow regimes in the drains of the coastal marshes and analysis of telemetry data from the land drainage pumps, this thesis investigates 1) the spatial distribution of the salt loading into the drain system in order to identify where management changes should be targeted and 2) assesses whether changes to the water level management in a nearby drainage area have had any impact on the salt load that is discharged from the pump. Research has shown an uneven distribution of salt loading across the coastal marshes. These differences appear to be driven by the nature of the drain-aquifer interaction in the individual marshes and the relative gradient differential produced between the marsh drainage ditches and the main drain at times of pump activity. The research indicates that restoration of the Upper Thurne water quality will necessitate scaling down water table level management to individual marshlands in order to ensure efficacy of measures. It also makes recommendations for further research to be carried out in the study area. There is insufficient data at the time of writing to suggest that raising water levels in an adjacent marshland has conclusively reduced saline discharges from the pumps since management controls were implemented. However, some lowering of salt concentrations was observed which appear to be distinct from climatic influences.
Keywords: aquatic species; poor water quality; land drainage pump; salt concentrations; salt loading; coastal marshes